1999
DOI: 10.1144/petgeo.5.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Variations in fracture system geometry and their implications for fluid flow in fractures hydrocarbon reservoirs

Abstract: Studies assembling high quality datasets of fracture systems (joints and faults) from four reservoir analogues are described. These comprise limestones (Ireland), sandstones (Norway and Saudi Arabia) and chalk (Denmark). These are used with existing information from the literature to review the major controls and scaling behaviour of fracture systems expected in reservoir rocks. Lithological layering was found to be important and two end-member fracture systems have been identified. In "stratabound" systems, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
257
0
22

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 449 publications
(285 citation statements)
references
References 37 publications
6
257
0
22
Order By: Relevance
“…In sandstones, aperture scaling may be described by a universal exponent [Hooker et al, 2014], whereas for carbonates variable exponents are inferred [Hooker et al, 2012, and references therein]. These different values are likely related to trends in lithology or mechanical units, which may constrain the growth of fractures, but no physical relation between these outcrop properties and scaling exponents has been observed [Odling et al, 1999;Bonnet et al, 2001;Hooker et al, 2012].…”
Section: Models For Aperture Predictionmentioning
confidence: 99%
“…In sandstones, aperture scaling may be described by a universal exponent [Hooker et al, 2014], whereas for carbonates variable exponents are inferred [Hooker et al, 2012, and references therein]. These different values are likely related to trends in lithology or mechanical units, which may constrain the growth of fractures, but no physical relation between these outcrop properties and scaling exponents has been observed [Odling et al, 1999;Bonnet et al, 2001;Hooker et al, 2012].…”
Section: Models For Aperture Predictionmentioning
confidence: 99%
“…Outcrop characterization studies have shown that natural fractures vary substantially in height, length, and aperture, as well as spacing and network connectivity (Gillespie et al, 1993;Odling, 1997;Odling et al, 1999), thus highlighting a large discrepancy between reality and the uniformity inherent in dual porosity model assumptions. Hence, discrete fracture models (DFMs) were developed to reduce the number of non-physical abstractions inherent in dual continuum models.…”
Section: Discrete Fracture Modelsmentioning
confidence: 99%
“…As previously described, natural fracture systems commonly show an asymmetrical distribution of fracture sizes, with numerous small fractures and fewer large fractures (Odling et al, 1999). It is not practical to treat small fractures explicitly in discrete fracture simulations.…”
Section: Comparison Of Edfm To An Unstructured Dfm and A Dual Permeabmentioning
confidence: 99%
“…Actually we can also see from Fig. 5b that the landscape coverage can lead to a curvature at the small scale in the density distribution of fracture lengths, which may be related to the socalled ''truncation effect'' (Pickering et al 1995;Bonnet et al 2001) that is always present in the length distribution plot of outcrop data (Davy 1993;Odling 1997;Odling et al 1999;Bour et al 2002;Davy et al 2010;Le Garzic et al 2011;Bertrand et al 2015;Lei et al 2015;Lei and Wang 2016).…”
Section: Discussionmentioning
confidence: 75%
“…The results have important implications for assessment of the statistical parameters derived based on natural fracture outcrops. To conduct field mapping, great efforts were often devoted to search sites with good quality exposures to keep them to a large extent free of vegetation (Odling 1997;Odling et al 1999;Belayneh and Cosgrove 2004). However, in some geological sites, it can be very difficult to avoid the groundcover effects, because embryophytes can form vegetation on the Earth's surface over different length scales, making the mapped outcrop containing unknown gap zones (Ghosh and Daemen 1993;Rawnsley et al 1998;Gillespie et al 2001;Bisdom et al 2017).…”
Section: Discussionmentioning
confidence: 99%